A retrospective study of glucose homeostasis, insulin secretion, sensitivity/resistance in non- transfusion-dependent β-thalassemia patients (NTD- β Thal): reduced β-cell secretion rather than insulin resistance seems to be the dominant defect for glucose dysregulation (GD) - De Sanctis, Vincenzo; Daar, Shahina; Soliman, Ashraf; Tzoulis, Ploutarchos; Yassin, Mohamed; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Aims: Non-transfusion - dependent β-thalassemias (NTD-βThal) can cause iron overload and serious iron-related organ complications as endocrine dysfunction, including glucose dysregulation (GD). Patients and methods: We retrieved data of all NTD- β Thal patients referred consecutively to a single Outpatient Italian Clinic from October 2010 to April 2023. All patients underwent a standard 3-h oral glucose tolerance test (OGTT) for analysis of glucose homeostasis, insulin secretion and sensitivity/resistance (IR), using conventional surrogate indices derived from the OGTT. The collected data in NTD- β Thal patients were compared to 20 healthy subjects. Results: Seventeen of 26 (65.3 %) NTD- β Thal patients (aged: 7.8 -35.1 years) had normal glucose tolerance, 1/26 (3.8 %) had impaired fasting glucose (IFG), 5/26 (19.2 %) impaired glucose tolerance (IGT), 1/26 (3.8%) IFG plus IGT and 2/26 (7.6%) plasma glucose (PG) level ≥155 mg/dL 1-h after glucose load. GD was observed exclusively in young adult patients; none of them had diabetes mellitus (DM). These findings were associated with a low insulinogenic index (IGI) and oral disposition index. HOMA-IR and QUICKI were not significantly different compared to controls. Interestingly, in young adult patients, ISI-Matsuda index was statistically higher compared to the control group, suggesting an increased insulin sensitivity. Conclusions: This study reported a high prevalence of GD in young adults with NTD- β Thal. The documented reduction of IGI rather than the presence of IR, indicates reduced insulin secretory capacity as the pathophysiological basis of dysglycemia that may represent a novel investigational path for future studies on the mechanism(s) responsible for GD in NTD- β Thal patients.